The Influence of Cancer Stage and Primary Cancer Location on the Occurrence of Breakthrough Pain (BTP) in Cancer Patients at Haji Medan Hospital - Rahma Rifda Fadilla Sury Lubis; Muhammad Jalaluddin Assuyuthi Chalil (UMSU, 2026)
Abstract: Background : The International Agency for Research on Cancer (IARC) in 2022 reported 20 million cancer patients worldwide. IARC also reported that the incidence of cancer in Indonesia reached 408,661 new cases in 2022. As many as 66% of cancer patients usually experience cancer pain as a complaint experienced by patients. Breakthrough Pain (BTP) generally occurs in patients with cancer cases, 40% to 93% of cancer patients experience BTP. Objective: To determine the effect of cancer stage and primary location of cancer on the incidence of BreakThrough Pain (BTP) in cancer patients at the Haji Medan Hospital. Results: of the 62 total respondents, 51 experienced cancer pain and 34 experienced (BTP). The majority of respondents who experienced BTP were women with primary cancer locations in the mammary glands and were already in the final stages of cancer. Conclusion: A significant relationship was found between cancer stage and primary location of cancer with the incidence of BTP at the Haji Medan Hospital.